Efficacy of Biostimulants on Growth, Flowering and Yield of Dendrobium var. Sonia White - Suvagiya, Dipti; Shah, H. P.; Chaudhary, S. M.; Singh, Alka; Vora, Saba (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during March, 2022–February, 2023 at Greenhouse Complex, Department of Floriculture and Landscape Architecture, ASPEE College of Horticulture, Navsari Agricultural University, Navsari, Gujarat, India to assess the effects of various biostimulants on the performance of Dendrobium var. Sonia White under naturally ventilated polyhouse conditions. Nine treatments were carried out at monthly intervals over a year in a Completely Randomized Design (CRD) with three repetitions, using a foliar spray of different biostimulants viz. Chitosan viz. 75, 100, 125 ppm; Brassinosteroid viz. 0.25, 0.50, 0.75 ppm; Novel Organic Liquid Nutrients at 2%; Gliricidia Nutrient Extract at 2%. The result indicated that among all treatments, the application of 0.75 ppm Brassinosteroid (T6) at monthly intervals resulted in maximum plant height (43.94 cm), leaf area (45.82 cm2) and chlorophyll content (0.478 mg g-1) after 12 months. In terms of flowering parameters, it also resulted in the highest number of spikes plant-1 (4.87), longest spike length (49.42 cm), highest number of florets spike-1 (12.01), longest floret length (7.59 cm), longest spike longevity (52.44 days), longest vase life (31.96 days) along with Highest Net realization (`Rs. 7457160 per ha-1) and BCR (2.03) in Dendrobium var. Sonia White.